Globalization - Yungchih Wang, George (IntechOpen, 2019)
Globalization is a process of interaction and integration among people, businesses, institutions, and governments of different countries in many aspects surrounding human lives. It is not a threat to sovereignty or a form of Westernization. This book discusses international economics and globalization, explores global business strategies, deliberates business ethics and corporate social responsibility, and examines other related aspects from a global perspective.